Dominant influence of HLA-B in mediating the potential co-evolution of HIV and HLA - Kiepiela, Photini; Leslie, Alasdair J.; Honeyborne, Isobella; Ramduth, Danni; Thobakgale, Christina; Chetty, Senica; Rathnavalu, Prinisha; Moore, Corey; Pfafferott, Katja J.; Hilton, Louise; Zimbwa, Peter; Moore, Sarah; et al. (Nature (London), 2004)
The extreme polymorphism in the human leukocyte antigen (HLA) class I region of the human genome is suggested to provide an advantage in pathogen defence mediated by CD8 + T cells 1 , 2 , 3 . HLA class I molecules present pathogen-derived peptides on the surface of infected cells for recognition by CD8 + T cells. However, the relative contributions of HLA-A and -B alleles have not been evaluated. We performed a comprehensive analysis of the class I restricted CD8 + T-cell responses against human immunodeficiency virus (HIV-1), immune control of which is dependent upon virus-specific CD8 + T-cell activity 4 , 5 . In 375 HIV-1-infected study subjects from southern Africa, a significantly greater number of CD8 + T-cell responses are HLA-B-restricted, compared to HLA-A (2.5-fold; P = 0.0033). Here we show that variation in viral set-point, in absolute CD4 count and, by inference, in rate of disease progression in the cohort, is strongly associated with particular HLA-B but not HLA-A allele expression ( P < 0.0001 and P = 0.91, respectively). Moreover, substantially greater selection pressure is imposed on HIV-1 by HLA-B alleles than by HLA-A (4.4-fold, P = 0.0003). These data indicate that the principal focus of HIV-specific activity is at the HLA-B locus. Furthermore, HLA-B gene frequencies in the population are those likely to be most influenced by HIV disease, consistent with the observation that B alleles evolve more rapidly than A alleles 6 , 7 , 8 . The dominant involvement of HLA-B in influencing HIV disease outcome is of specific relevance to the direction of HIV research and to vaccine design.